매뉴얼 트레파인과 펨토초레이저를 이용한 전층각막이식의 장기 임상결과 비교 - 소하림(Ha-Rim So), 김선주(Seon-Joo Kim), 주천기(Choun-Ki Joo), 황유숙(You-Sook Hwang), 변용수(Yong-Soo Byun), 정소향(So-Hyang Chung), 김현승(Hyun-Seung Kim) (Daihan angwa haghoi jabji, 2020)
목적: 펨토초레이저를 이용한 전층각막이식을 시행하여 임상결과를 매뉴얼 트레파인을 이용한 전층각막이식과 비교하여 보고하고자 한다. 대상과 방법: 매뉴얼 트레파인을 이용한 전층각막이식을 받은 21안, 펨토초레이저를 이용한 전층각막이식을 받은 29안에 대해 최대교정시력, 굴절난시, 각막난시, 각막내피세포수, 이식 거부, 기능부전 등의 술 후 임상결과를 비교하였다. 결과: 수술 후 1, 3, 6, 12, 18개월에 측정한 최대교정시력은 매뉴얼군은 logMAR 1.21, 1.28, 1.25, 1.14, 1.43, 펨토초레이저군은 logMAR 0.82, 0.71, 0.78, 0.49, 0.56으로 모든 기간에서 펨토초레이저군이 매뉴얼군에 비해 높은 시력을 유지하였다. 굴절난시는 매뉴얼군은 5.13, 6.35, 5.28, 5.18, 6.36 diopters (D), 펨토초레이저군은 6.09, 6.33, 5.14, 5.23, 4.89 D, 각막난시는 매뉴얼군은 5.40, 6.45, 6.30, 5.64, 5.78 D, 펨토초레이저군은 6.17, 6.24, 5.72, 5.02, 4.83 D이며 굴절난시는 수술 후 18개월째, 각막난시는 수술 후 12, 18개월째에 펨토초레이저군에서 유의하게 난시 도수가 낮았다. 각막내피세포수, 이식 거부 및 기능부전은 두 군에서 유의한 차이를 보이지 않았다. 결론: 펨토초레이저를 이용한 전층각막이식은 매뉴얼 트레파인을 이용한 전층각막이식과 비교하여 시력회복이 좋고 굴절난시와 각막난시가 적으며, 창상부의 안정성이 더 좋은 장점이 있으므로 전층각막이식 시에 고려할 수 있는 하나의 수술 방법이다. Purpose: We compare the clinical outcomes of femtosecond-laser penetrating keratoplasty and penetrating keratoplasty performed using a manual trephine. Methods: The clinical outcomes of 21 eyes that underwent penetrating keratoplasty using a manual trephine and 29 eyes that underwent femtosecond-laser penetrating keratoplasty were compared in terms of best-corrected visual acuity, refractive and corneal astigmatisms, endothelial cell counts, and graft rejection and failure. Results: The best-corrected visual acuities measured 1, 3, 6, 12, and 18 months after surgery were logMAR 1.21, 1.28, 1.25, 1.14, and 1.43 for the manual trephine group and logMAR 0.82, 0.71, 0.78, 0.49, and 0.56 for the femtosecond-laser group; the latter group thus exhibited better visual acuity at all times. The refractive astigmatism values were 5.13, 6.35, 5.28, 5.18, and 6.36 diopters (D) for the manual trephine group and 6.09, 6.33, 5.14, 5.23, and 4.89 D for the femtosecond-laser group. The corneal astigmatism values were 5.40, 6.45, 6.30, 5.64, and 5.78 D for the manual trephine group and 6.17, 6.24, 5.72, 5.02, and 4.83 D for the femtosecond-laser group. The refractive astigmatism was significantly lower at 18 months after surgery and the corneal astigmatism was significantly lower at both 12 and 18 months after surgery in the femtosecond-laser group. None of endothelial cell count, graft rejection or failure rate, differed significantly between the two groups. Conclusions: Femtosecond-laser-enabled keratoplasty affords better visual recovery, less refractive and corneal astigmatism, and better wound stability than does penetrating keratoplasty using a manual trephine. KCI Citation Count: 0